2001
DOI: 10.1002/sia.1141
|View full text |Cite
|
Sign up to set email alerts
|

Infrared microspectroscopic studies on the pitting of AA2024‐T3 induced by acetone degreasing

Abstract: Acetone degreasing of aluminum alloy AA2024-T3, as per the ASTM E1078-97 cleaning protocol, showed that copper-rich intermetallic particles acted as a photocatalyst in the presence of moisture to convert the acetone remaining on the surface to acetic acid. In this work, using synchrotron infrared microspectroscopy (SIRMS), we have investigated further the acetone-induced pitting of AA2024-T3 that was shown earlier using XPS. Using SIRMS prior to sodium chloride mist exposure shows the presence of carboxyl grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Previous work using spatially resolved chemical analysis has demonstrated the effect of IMC on CCC composition and structure. 1,32,39 Specifically, SIRMS data from a CCC grown on AA2024-T3 showed that cyanide, hydroxyl and chromate are selectively deposited with respect to certain IMCs on the Al alloy. Xia et al 24 have demonstrated that the ferricyanide is a mediator that rapidly oxidizes aluminum in the acceleration mechanisms for CCC formation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work using spatially resolved chemical analysis has demonstrated the effect of IMC on CCC composition and structure. 1,32,39 Specifically, SIRMS data from a CCC grown on AA2024-T3 showed that cyanide, hydroxyl and chromate are selectively deposited with respect to certain IMCs on the Al alloy. Xia et al 24 have demonstrated that the ferricyanide is a mediator that rapidly oxidizes aluminum in the acceleration mechanisms for CCC formation.…”
Section: Resultsmentioning
confidence: 99%
“…Further information on the VUV ring can be found elsewhere. 19 The synchrotron provided a 'white' light source about 1000 times brighter than the typical FTIR source and a 1200 K thermal source (sometimes called a 'globar'). The synchrotron light pulsed at 50 MHz with pulse widths of 500 ps and was introduced into a commercial FTIR microspectrometer.…”
Section: Synchrotron Infrared Microspectroscopymentioning
confidence: 99%
“…All spectra were obtained in reflection mode. Further details of this system and technique have been provided elsewhere by Carr et al 21,22 X-ray absorption near-edge structure spectroscopy (XANES)…”
Section: Synchrotron Infrared Microspectroscopy (Sirms)mentioning
confidence: 99%